GENRE CHARACTERISTICS OF STORIES BY ODILE YAKUBOV (Scientific journal of the Fergana State University, 2024)
The article highlights the features of the artistic skill of writing the genre features of the stories of the people's writer of Uzbekistan Odil Yakubov. The author’s contribution to Uzbek storytelling of the 20th-21st centuries is shown through the analysis of the stories “Matluba” and “Tilla Uzuk”. These stories analyze aspects characteristic of the artist's style.